Wage Mobility : Do Institutions Make a Difference? : A Replication Study Comparing Portugal and the UK - Ana Rute Cardoso (Institute for the Study of Labor (IZA), 2004)
This study compares wage mobility in Portugal and the UK, replicating the work by Dickens (2000) and progressing to discuss the impact of differences in the institutional framework, which is more regulated and centralized in Portugal, with minimum wages, employment protection, and collective bargaining widely applied. Results indicate that both countries became more unequal and less mobile labour markets, having departed from similar levels in mid-80s. The evidence does not support the idea that a more regulated institutional framework reduces individual mobility within the wage distribution.
Keywords: J60; J31; 330; wage mobility; wage dispersion; Lohn; Lohnstruktur; Soziale Mobilität; Arbeitsmarktflexibilisierung; Schätzung; Vergleich; Grossbritannien; Portugal